The Palatinate Church Order of 1563 - Thompson, Bard (Church history, 1954)
The ground and provocation of the German Reformed Church are first considerations in the appreciation of its character. It is understood that the Palatinate Church Order of 1563, containing the Heidelberg Catechism and the Palatinate liturgy, introduced a permanent Reformed tradition to Germany. It should also be understood that that kirchenordnung represented the effort of a Melanchthonian church to maintain its evangelical consciousness against the pressures of Gnesio-Lutheranism. Later Palatinate religion arose thus from the ground of Melanchthonianism and in the context of the Crypto-Calvinist controversy—the creation of Zacharius Ursinus, a pupil of Melanchthon and Martyr, and more deeply of John a Lasco, the Polish reformer whose influence in this connection remains untold.